Fiscal Systems for Hydrocarbons : Design Issues - Tordo, Silvana (Herndon : World Bank Publications, 2007)
Although host governments and investors may share one common objective - the desire for projects to generate high levels off revenue - their other goals are not entirely aligned. Host governments aim to maximize rent for their country over time, while achieving other development and socioeconomic objectives. Investors aim to ensure that the return on investment is consistent with the risk associated with the project, and with their corporations' strategic objectives. To reconcile these often conflicting objectives, more and more countries rely on transparent institutional arrangements and flexible, nuetral fiscal regimes. This paper examines the key elements of the legal and fiscal frameworks utilized in the petroleum sector and aims to outline desirable features that should be considered in the design of fiscal policy with the objective of optimizing the host government's benefits, taking into account the effect this would have on the private sector's investment.
26. Government Participating Interest-Field A -- LIST OF FIGURES -- 1. The Project Cycle -- 2. Petroleum Legal Arrangements -- LIST OF GRAPHS -- 1. Government Take and Project IRR at Different Levels of Cost Recovery Limit-Field A -- 2. Government Take and Project IRR at Different Levels of Cost Recovery Limit-Field B -- 3. Government Take and Project IRR at Different Levels of Cost Recovery Limit-Field C -- 4. Government Take and Project IRR at Different Levels of Cost Recovery Limit-Field D -- 5. Government Take and Project IRR at Different Price Levels-Field A -- 6. Government Take and Project IRR at Different Price Levels-Field B -- 7. Government Take and Project IRR at Different Price Levels-Field C -- 8. Government Take and Project IRR at Different Price Levels-Field D.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2017. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Petroleum industry and trade -- Government policy; Electronic books